ENERGY EFFICIENT TRANSMISSION USING OPTICAL ACCESS NETWORK: ISSUES AND CHALLENGES - T, Senthil Kumar; V, Mohan; S, Senthilkumar (International Journal of Engineering Science Technologies, 2023)
Everlasting increase of connected devices and users in communication networks carry out enormous traffic volumes. This reason places the network in a position to fine tune the energy consumption in proposal and attentive operations. Optical transmission technologies are a momentous paradigm which brings down the overall energy consumption in communication networks. This advantage increases an interest on research to improve the energy saving opportunities of optical networks. Regardless of this most vibrant research few unanswered questions direct the researchers to set effort on resolving the issues in energy efficient optical networks. Shannon limit and parallelism to support higher capacities is essential in approaching optical systems also without reducing the network performance parameters such as latency, reliability and survivability, energy consumption of optical networks must be laid out as it affects quality of services. New generation network services like optical cloud and fixed mobile convergence have necessity to meet out the end-to-end energy optimization. All these factors enlighten research area towards energy efficiency in optical network transmission. This special research work reconnoiters and consolidates the earlier research models related to energy efficient transmission in optical networks